Research on the molecular dynamics of coalbed methane diffusion and adsorption in reservoir pores under different factors - Xuefan Wang; Jianwei Zhong; Ziyang Zhang; Xu Zeng; Rui Shen; Ze Deng; Nan Wang (Energy Exploration & Exploitation)
The migration and diffusion of coalbed methane (CBM) are impeded by adsorption in pore channels, resulting in a significant portion of CBM being trapped in the reservoir and thereby reducing the efficiency of CBM extraction. Investigating the adsorption and diffusion behavior of CBM in reservoirs is crucial for optimizing CBM extraction. In this study, we developed a theory based on the basic geological characteristics of coal beds and the adsorption state of CBM, focusing on the transition state of adsorption gas diffusion of surface diffusion gas molecules. We explored the impact of various factors on the diffusion coefficients and adsorption capacity of CBM, elucidating the underlying reasons for variations in CBM adsorption and diffusion through molecular dynamics simulations. Our findings reveal that CBM undergoes simultaneous adsorption and desorption on the surface of coal beds, with adsorption conforming to the Langmuir monomolecular layer adsorption. Increasing reservoir temperature leads to a reduction in methane adsorption and a gradual increase in diffusion coefficient. For instance, at 80 °C, methane adsorption decreases to 0.5 mg/m 3 , while the diffusion coefficient increases to 4 × 10 −9  m 2 /s. Moreover, the presence of water in coal beds significantly weakens CBM adsorption capacity, with a water content of 0.5% resulting in a minimal adsorption capacity of 0.5 mg/m 3 . Additionally, increasing coal bed pressure enhances CBM adsorption capacity but decreases the diffusion coefficient. For example, a reservoir pressure of 30 MPa increases CBM adsorption capacity to 0.65 mg/m 3 , while reducing the diffusion coefficient to 2.5 × 10 −9  m 2 /s. Overall, our study demonstrates that geological conditions, such as temperature, water content, and pressure, play crucial roles in shaping CBM adsorption and diffusion behavior. By understanding these environmental factors, we can effectively manipulate CBM diffusion and adsorption capacity, thereby providing essential insights and foundational data for CBM exploitation.